(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines the comparative performance of non-performing assets (NPAs) among leading non-banking financial companies in India during the period of 2011-2015. Among these, Spearman’s correlation study indicated that Bajaj Finance was observed a positive correlation with a significant value between revenue versus gross NPA (P<0.04), profit after tax versus gross NPA (P<0.04), and return on assets (ROA) versus gross NPA (P<0.005) found with negative correlation. In the case of Muthoot Finance, there was a positive correlation with statistically significant value observed between return on assets versus gross NPA (P<0.04) and net NPA (P<0.05) while for Reliance Capital, there was a positive correlation with statistically significant value observed between revenue versus provision of NPA (P<0.04) and PAT versus provision of NPA (P<0.04). Moreover, yearly trend analysis revealed that Muthoot Finance was better concerning revenue generation and lower NPA values compared to Bajaj Finance and Reliance Capital.